Anti-inflammatory activity of naringin and the biosynthesised naringenin by naringinase immobilized in microstructured materials in a model of DSS-induced colitis in mice - Amaro, Maria Ines (2015)
A great number of antioxidants are naturally present in citrus juice, being responsible for their potentially protective action against inflammation. Naringin, a bitter compound, in citrus, is hydrolysed by naringinase into tasteless naringenin and to rhamnose and glucose. The aim of this study was to evaluate the anti-inflammatory activity of naringin and naringenin in an acute model of induced colitis in mice. Microstructured particles were used for naringinase immobilization. The influence of naringin and naringinase concentration on the bioconversion was evaluated through a central composite design. Colitis was induced by feeding mice 7% dextran sodium sulphate (DSS) dissolved in drinking water for 5 days. Intestine dry/wet weight ratio (indicator of intestine edema), nitrates/nitrites (indicators of inflammatory process), and tissue malondialdehyde levels (indicator of lipid peroxidation) were evaluated. Our results indicate that treatment with both naringin and naringenin significantly reduced the formation of intestine edema, suggesting an anti-inflammatory activity in this model of colitis in mice. (C) 2009 Elsevier Ltd. All rights reserved.. - Fundacao para a Ciencia e Tecnologia, Portugal [SFRH/BD/30716/2006]. - Helder Vila Real was supported by Fundacao para a Ciencia e Tecnologia, Portugal. Grant No. SFRH/BD/30716/2006.